Marketing Mix as a Strategy Increase Hospital Visits - Adipradana, Wendy Rosalinda; Khoirina, Nadya; Rahajeng, Argitta Della Ayu (Prosiding Seminar, 2023)
The marketing mix is a strategy to increase hospital visits by providing information about products and services, prices, place determination, promotion, service providers, processes, physical facilities, and the provision of customers (8 P). The increasing number of health service facilities causes the hospital to determine the right strategy to survive and develop. Increasing public awareness and demand for health services can be a significant opportunity for the hospital. This study aims to determine the marketing mix's implementation as a strategy to increase hospital visits. The research method used qualitative (literature study) and is explained descriptively. The result of this study indicates that the marketing mix is a marketing strategy that must be planned routinely to increase hospital visits